The Digital Heartbeat: Using Wearables to Revolutionize Cardiovascular Health Monitoring - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The landscape of cardiovascular health monitoring is undergoing a profound transformation, driven by the rapid advancement of wearable technology and artific...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care